2017
DOI: 10.7863/ultra.16.04012
|View full text |Cite
|
Sign up to set email alerts
|

Role of Contrast‐Enhanced Sonography in the Evaluation of Axillary Lymph Nodes in Breast Carcinoma: A Monocentric Study

Abstract: Contrast-enhanced sonography appears to be a method with high accuracy for characterization of axillary lymph nodes, very close to the reference-standard sentinel lymph node biopsy. This technique seems to have overall high sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
(52 reference statements)
1
6
0
5
Order By: Relevance
“…In addition, some studies [8-10, 47, 48] reported that SLNs and LCs were visualized with ultrasound contrast agents and our study confirmed these findings. However, in previous studies, the ultrasound contrast agents used to detect metastatic involvement in the lymph nodes were injected IV, since metastatic lymph nodes may exhibit peripheral and mixed vascularity due to tumor angiogenesis [49-51]. Thus, ultrasound contrast agents injected IV were intended to enhance the micro- and neo-vessels in the lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies [8-10, 47, 48] reported that SLNs and LCs were visualized with ultrasound contrast agents and our study confirmed these findings. However, in previous studies, the ultrasound contrast agents used to detect metastatic involvement in the lymph nodes were injected IV, since metastatic lymph nodes may exhibit peripheral and mixed vascularity due to tumor angiogenesis [49-51]. Thus, ultrasound contrast agents injected IV were intended to enhance the micro- and neo-vessels in the lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…При инъекции контрастного препарата эффект усиления проявляется у ворот узла на 10-15 с с дальнейшим однородным усилением кортекса без дефектов перфузии. Вымывание препарата начинается на 40-45 с и как правило прекращается после 60-90 с [38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: рис 2 распространенные причины диагностических ошибок при unclassified
“…Оценивая ценность проведения таких дополнительных расчетов G. Agliata и соавт. [49] отмечают, что из-за относительного усложнения и удлинения процедуры некоторые из этих исследований показывают снижение специфичности по сравнению с прямой визуальной интерпретацией.…”
Section: стоматология 3 2019unclassified
See 1 more Smart Citation
“…Pojedini istraživači su objavili veliku preciznost u određivanju malignih aksilarnih limfnih nodusa, kombinovanjem dva modaliteta (ultrazvuk i biopsija tankom iglom). [1][2][3][4][5][6] Međutim za FNAB je potrebna velika stručnost i saradnja sa iskusnim citologom, i više zavisi od operatora u poređenju sa osnovnom ekscizionom biopsijom. Kliničko ispitivanje i mamografija ne predstavljaju ispitivanja koju su dovoljna u određivanju metastatski izmenjenih aksilarnih limfnih nodusa.…”
Section: Diskusijaunclassified